Structuring organisations for the smooth integration of artificial intelligence - Ivchyk, Vasyl (International Center of Scientific Research, 2025)
This study seeks to investigate the challenges organizations face in successfully adopting. Artificial Intelligence (AI), with an emphasis on psychological, organizational, and ethical barriers. The research aims to develop strategies that reduce resistance, build trust, and enable the smooth integration of AI technologies into business operations. Methodology. A qualitative approach was employed through a comprehensive review of existing literature and analysis of real-world case studies to identify the root causes of resistance to AI. The study focuses on psychological fears, organizational obstacles, and ethical concerns while presenting strategic frameworks and actionable solutions to overcome these issues. Findings. Psychological resistance stems from fears of job displacement and skepticism toward AI, whereas organizational barriers arise from misaligned goals and ingrained cultural attitudes. Ethical concerns, including bias, accountability, and data privacy, add further complexity to AI adoption. Recommended strategies highlight the importance of transparency, aligning AI initiatives with organizational objectives, implementing governance systems, and addressing ethical considerations to improve adoption efforts. Practical Applications. The research provides actionable guidance for business leaders and policymakers, including cultivating openness, investing in employee training, and upholding ethical principles. These steps are crucial for building trust and achieving stakeholder alignment. Original Contribution. This study introduces an innovative framework for addressing resistance to AI, combining psychological, organizational, and ethical dimensions. By integrating theoretical analysis with practical strategies, it equips organizations to realize AI’s transformative potential while maintaining alignment with societal and moral values.
Keywords: artificial intelligence; integration; structuring organisations; businesses; competition; digital innovations